Review of the fish–parasitic genus Cymothoa Fabricius, 1793 (Isopoda, Cymothoidae, Crustacea) from the southwestern Indian Ocean, including a new species from South Africa - Hadfield, Kerry A.; Smit, Nico J.; Bruce, Niel L. (Magnolia Press, 2013)
The genus Cymothoa Fabricius, 1793 is revised for southwestern Indian Ocean waters. Cymothoa borbonica Schioedte & Meinert, 1884 and C. eremita Brünnich, 1783 are redescribed. Cymothoa rotundifrons Haller, 1880, from Mauritius lacks type material and the host is unknown, therefore it is here relegated to nomen dubium. Cymothoa sodwana sp. nov., from Trachinotus botla (Carangidae), collected from the Kwazulu-Natal coast of South Africa, is described and is distinguished by the large, ovoid, hunched body with rugose dorsal surfaces; the anterolateral angles of pereonite 1 are narrow and rounded reaching half the length of the cephalon; the ischium of pereopod 7 has a large protrusion and pereonite 7 which laterally overlaps the pleon margins, extending posteriorly to the pleotelson
Keywords: Buccal cavity; fish parasite; Indian Ocean; redescription; Cymothoa sodwana